Explain how Differentiation by the chain rule works

If the expression to be differentiated is a (differentiable) function of another (differentiable) function, then the chain rule must be applied. For example y= f(g(x)), where f and g are both differentiable, then dy/dx = f'(g(x)).g'(x). To simplify this, it can be looked at as a simple substitution:
Let g(x)=u, then, the chain rule states that, dy/dx=(du/dx).(dy/du). For example, should the expression to be differentiated be (cos(x))^2, then let u=cosx, du/dx = -sin(x), y=u^2, dy/du=2u, therefore dy/dx = -sin(x).2(cos(x)).

Answered by Gwyndaf O. Maths tutor

3325 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Let N be an integer not divisible by 3. Prove N^2 = 3a + 1, where a is an integer


How do I find the points of intersection between two curves?


Differentiate y=x^2cos(x)


Integrate cos^2x + cosx + sin^2x + 3 with respect to x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences